Ultra-High-Performance Fiber-Reinforced Concrete an Alternative Material for Rehabilitation and Strengthening of Concrete Structures: A Review. (May 2020) - Nursyamsi, Nursyamsi; Tarigan, Johannes; Abu Bakar, B.H.; Hardjasaputra, Harianto
Abstract: Ultra-High-Performance Fiber-Reinforced Concrete (UHPFRC) is a more powerful concrete material compared to the conventional concrete. With its low permeability level, UHPFRC possesses an exceptional durability. Therefore, it is strongly recommended as a material for rehabilitation and strengthening for concrete structures. In addition to its performances, UHPFRC also holds superior mechanical properties, including compressive strength, split tensile strength, ductility and workability. In general, UHPFRC dimensions are categorized to be thinner than the conventional concrete, making it as an advantage of UHPFRC application. However, since all fine and coarse aggregates in the conventional concrete are replaced with very fine aggregates, UHPFRC is unable to be fabricated considering its availability in certain location. To date, researches on UHPFRC as a reinforced material have developed significantly, covering the discovery to increase the compressive strength, flexural strength, high bonding strength, durability and thickness. The aim of this paper is to review previous findings of UHPFRC to be utilized as conventional concrete repair material.